Does carrier velocity saturation help to enhance fmax in graphene field-effect transistors?. Issue 9 (10th August 2020) - Feijoo, Pedro C.; Pasadas, Francisco; Bonmann, Marlene; Asad, Muhammad; Yang, Xinxin; Generalov, Andrey; Vorobiev, Andrei; Banszerus, Luca; Stampfer, Christoph; Otto, Martin; Neumaier, Daniel; Stake, Jan; et al.
Abstract : A drift–diffusion model including self-heating effects in graphene transistors to investigate carrier velocity saturation for optimal high frequency performance. Abstract : It has been argued that current saturation in graphene field-effect transistors (GFETs) is needed to get optimal maximum oscillation frequency ( f max ). This paper investigates whether velocity saturation can help to get better current saturation and if that correlates with enhanced f max . We have fabricated 500 nm GFETs with high extrinsic f max (37 GHz), and later simulated with a drift–diffusion model augmented with the relevant factors that influence carrier velocity, namely: short-channel electrostatics, saturation velocity effect, graphene/dielectric interface traps, and self-heating effects. Crucially, the model provides microscopic details of channel parameters such as carrier concentration, drift and saturation velocities, allowing us to correlate the observed macroscopic behavior with the local magnitudes. When biasing the GFET so all carriers in the channel are of the same sign resulting in highly concentrated unipolar channel, we find that the larger the drain bias is, both closer the carrier velocity to its saturation value and the higher the f max are. However, the highest f max can be achieved at biases where there exists a depletion of carriers near source or drain. In such a situation, the highest f max is not found in the velocity saturation regime, but where carrier velocity is far below its saturated value and the contribution of the diffusion mechanism to the current is comparable to the drift mechanism. The position and magnitude of the highest f max depend on the carrier concentration and total velocity, which are interdependent and are also affected by the self-heating. Importantly, this effect was found to severely limit radio-frequency performance, reducing the highest f max from ∼60 to ∼40 GHz.